Tumour Response After Palliative Radiotherapy: Influence on Head and Neck Cancer Patients Survival: Resposta Tumoral Após Radioterapia Paliativa: Influência na Sobrevivência dos Doentes de Cabeça e Pescoço - Cruz, Mafalda (2018)
INTRODUCTION: Palliative radiotherapy provides improved quality of life in head and neck cancer patients. Little is known regarding the influence of palliative radiotherapy on locoregional control and survival rates. Our objective was to evaluate tumour response after palliative radiotherapy for head and neck cancer patients and its influence on overall survival.MATERIAL AND METHODS: Retrospective study of patients diagnosed with head and neck cancer who completed palliative radiotherapy to primary local-regional sites between January 2014 and December 2016. Tumour response patterns were evaluated following a cervical and chest computed tomography performed 4-6 weeks after the end of the treatment. Differences between groups were compared using ANOVA and Chi-square test.RESULTS: We included 53 patients in our study. Radiotherapy schemes were 50 Gy/20 fr in 35.8% of our patients, 30 Gy/10 fr (32.1%), 37.5 Gy/15 fr (18.9%) and 40 Gy/20 fr (13.2%). A percentage of 61.2% of the patients had a partial response on computed tomography and 10.2% had complete response. After a mean follow-up period of 27.2 months, mean overall survival was 9.55 months (± 9.3). There were no differences in overall survival between the four radiotherapy schemes (p = 0.41). Patients who had better tumour response on computed tomography had a propensity for longer overall survival (p = 0.011).CONCLUSION: There is no consensus regarding the choice of the optimal radiotherapy fractionation scheme used in palliative care of head and neck cancer patients. Patients with advanced incurable head and neck cancer have a poor prognosis but the addition of palliative radiotherapy provides better local-regional control of the disease with the possibility of longer survival rates.